PROTECTION OF CHILDREN'S RIGHTS IN CHOOSING RELIGION IN INDONESIA - Erdian; Natsir Asnawi (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
The protection of children's rights in choosing religion and practicing worship is a constitutional issue that is increasingly relevant in a democratic legal country that upholds human rights. Although freedom of religion is guaranteed in the 1945 Constitution of the Republic of Indonesia, the practice of positive legal regulation still shows the tension between children's rights, parental authority in parenting, and state obligations through the national education system. This study aims to analyse the normative construction of the protection of children's rights to freedom of religion and worship, as well as to test the coherence of its regulation in the perspective of human rights. The main questions asked are what is the position of children's rights in conflict with parental rights and what is the appropriate model of protection within Indonesia's positive legal framework. This research uses a normative juridical method with a legislative and conceptual approach. Data was collected through literature studies on relevant primary, secondary, and tertiary legal materials, then analysed qualitatively to assess the consistency and harmonization of norms. The results of the study show that constitutional guarantees for children's religious freedom exist, but they are not fully coherent when dealing with sectoral norms that give dominant space to parents and the education system. This research offers a child-centred rights protection model based on the principles of the best interests of children and evolving capacities as a normative harmonization framework. In conclusion, the protection of children's rights to religious freedom requires a clearer affirmation of normative parameters as well as corrective mechanisms that are responsive to family conflicts.